1988
DOI: 10.1161/01.hyp.12.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Release of fatty acids by perfused vascular tissue in normotensive and hypertensive rats.

Abstract: SUMMARY The release of fatty acids from perfused mesenteries of spontaneously hypertensive rats (SHR) and control Wistar-Kyoto rats (WKY) was studied. The release of the prostaglandin precursors dihomogammalinolenic acid, arachidonte acid, and ekosapentaenoic acid was reduced in SHR when compared with age-matched WKY. The release of all other fatty acids detected in the effluent was also reduced. The differences in fatty add release were evident even when tissue levels of the fatty acids were similar or higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Although the proportion of AA in the mesenteric vessels of SHR is lower than in controls (34), the fraction of AA in the SHR aorta is higher than in controls at 1 and 3 mon. These results are similar to those for the kidney and indicate that the SHR aorta has the potential to synthesize more cyclooxygenase products than the aorta of age-matched WKY or may undergo changes in the incorporation of PUFA in the sn-2 position of membrane phospholipids.…”
Section: Discussionmentioning
confidence: 62%
“…Although the proportion of AA in the mesenteric vessels of SHR is lower than in controls (34), the fraction of AA in the SHR aorta is higher than in controls at 1 and 3 mon. These results are similar to those for the kidney and indicate that the SHR aorta has the potential to synthesize more cyclooxygenase products than the aorta of age-matched WKY or may undergo changes in the incorporation of PUFA in the sn-2 position of membrane phospholipids.…”
Section: Discussionmentioning
confidence: 62%
“…In another study (Bayorh et al 1989) chronic administration of eicosapentaenoic acid subcutaneously for 8 weeks lowered blood pressure in SHR significantly compared to WKY rats. In male SHR, some find that blood pressure decreases after supplementation with fish oil (high w-3; Hoffmann et al Von Au et al 1988;Brandle & Jacob 1990), dietary borage oil (Engler et al 1992;Engler 1993) or corn oil (high w-6; Mtabaji et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the effects of high PUFA intakes on blood pressure remain controversial in human studies as well as in animal models. Increased dietary PUFA have been reported by some investigators to decrease blood pressure in spontaneously hypertensive rats (SHR; Hoffmann et al 1986;Mtabaji et al 1988;Von Au et al 1988;Bayorh et al 1989;Karanja et al 1989;Brandle & Jacob, 1990;Yin et al 1990;Engler et al 1992); however, others find no significant effects or actual increases in blood pressure (McGreger et al 1981;Codde et al 1989;Croft et al 1988;Kingsley & Snyder 1988;Watanabe et al 1989). Since hypertension is one of the risk factors for developing coronary heart disease, many people are motivated to increase dietary PUFA to achieve the cardiovascular beneficial effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sunano et al showed that endothelial dysfunction was profoundly involved in the development of hypertension 5) . Studies of animals and humans with hypertension have shown that dietary fish oil rich in n-3 polyunsaturated fatty acids (PUFA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) has a blood pressure-lowering effect [6][7][8][9] . Data from clinical trials have consistently shown that fish oil supplements can improve endothelial function [10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%